2012
DOI: 10.1007/s00404-012-2443-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of gynecological, urological, and psychiatric factors in chronic pelvic pain

Abstract: Chronic pelvic pain is a syndrome in which biological and psychosocial factors play a role. Laparoscopy for chronic pelvic pain is an operation based on the "see and fight" principle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…In one study of 44 patients adhesionlysis and ovarian cyst removal was done in 8, endometrioma excision was done In 9 and salpingectomy and endometrioma cauterization was done in one patient each. 4 Other studies have also shown almost similar results and interesting findings. 12,13,14,15 limitation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In one study of 44 patients adhesionlysis and ovarian cyst removal was done in 8, endometrioma excision was done In 9 and salpingectomy and endometrioma cauterization was done in one patient each. 4 Other studies have also shown almost similar results and interesting findings. 12,13,14,15 limitation.…”
Section: Discussionsupporting
confidence: 57%
“…In contrast to one study there was a significant difference between two Groups in terms of Patients age. 4 The incidence of CPP was found to be highest in Para 2 (41.81%) and lowest in cases of infertility (1.87%). In Group B, maximum number of cases were Para 2 (45.45%).…”
Section: Discussionmentioning
confidence: 85%
“…Its prevalence has been estimated as between 12% and 29%. 8 Laparoscopy in cases of chronic pelvic pain can be useful for diagnosing diseases such as endometriosis, adhesions, ovarian cysts and pelvic inflammatory disease. In cases of endometriosis, laparoscopy is the gold standard for diagnosis, in addition to enable staging (endometriosis grades 1, 2, 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…It may also be due to psychological disorders and neurological diseases. Various gynecological causes responsible for CPP are endometriosis, Pelvic Inflammatory Disease (PID), adhesions, pelvic congestion syndrome, adenomyosis, ovarian neoplasm, ovarian remnant, residual syndrome and leiomyoma 3 .…”
Section: Introductionmentioning
confidence: 99%